Acute Response Heartbeat of Single Artistic Athletes IPSI Sukoharjo during Championship Simulation - Syamsudin, Fajar; Amrulloh, Aziz; Indardi, Nanang (UNIVERSITAS NEGERI MAKASSAR, 2023)
Research on the sport of pencak silat regarding heartbeat is rarely studied, heartbeat is a precursor to the intensity of an athlete's training, a benchmark for the readiness of an athlete's performance. This study aims to understand the response of the heart when carrying out a match simulation performance in a single artistic category pencak silat athletes. The subject used was a single artistic athlete from IPSI Sukoharjo who advanced to the PORPROV Central Java Championship (Central Java Provincial Sports Week), a heart rate monitor was used to find out how his heartbeat responded during appearances. The results of this study, the first second to start the simulation moves, namely 142bpm (74% max. of heartbeat), then in the first 10 seconds it is 155bpm (77% max. of heartbeat), the first 20 seconds is 168bpm (84% max. of heartbeat), then increasing slowly and steadily 180-185bpm (90-92% max. of heartbeat) in the 01.50 to 03.00 minutes. This study concludes that the heart rate will always be in rhythm with the intensity of the movements carried out by the athlete, the more maximal the movements carried out, the higher the heart rate, up to the maximum limit of his ability.